Experimental and numerical investigation of the impact of helical coil targets on laser-driven proton and carbon accelerations - C. L. C. Lacoste; E. Catrix; S. Vallières; A. Hirsch-Passicos; T. Guilberteau; M. Lafargue; J. Lopez; I. Manek-Hönninger; S. Fourmaux; D. Raffestin; E. d’Humières; P. Antici; et al. (Matter and Radiation at Extremes)
Laser-driven ion acceleration, as produced by interaction of a high-intensity laser with a target, is a growing field of interest. One of the current challenges is to enhance the acceleration process, i.e., to increase the produced ion energy and the ion number and to shape the energy distribution for future applications. In this paper, we investigate the effect of helical coil (HC) targets on the laser–matter interaction process using a 150 TW laser. We demonstrate that HC targets significantly enhance proton acceleration, improving energy bunching and beam focusing and increasing the cutoff energy. For the first time, we extend this analysis to carbon ions, revealing a marked reduction in the number of low-energy carbon ions and the potential for energy bunching and post-acceleration through an optimized HC design. Simulations using the particle-in-cell code SOPHIE confirm the experimental results, providing insights into the current propagation and ion synchronization mechanisms in HCs. Our findings suggest that HC targets can be optimized for multispecies ion acceleration.